The Environment‐poverty Nexus in Evaluation: Implications for the Sustainable Development Goals. Issue 3 (23rd June 2016) - Uitto, Juha I.
Abstract: The article emphasizes the importance of evaluation in the context of sustainable development. It focuses on the so called environment‐poverty nexus where issues of environmental conservation and management meet the social and economic development needs. Given the threats to the global environment and the forces of economic development that work against it, it is crucial that environmental policies, strategies, programmes and projects are designed and implemented in an effective manner producing lasting impacts. Evaluation is a central tool for analysing what works, why and under what circumstances to inform policy making and programme design. Environmental evaluation faces specific challenges due to the complex nature of the environment‐poverty nexus. Based on a review of evaluation literature and practical experiences with evaluations conducted on the nexus in the international development arena, the article draws lessons for evaluating sustainable development. It concludes by suggesting that strong evaluation be built into the new Sustainable Development Goals. Abstract : The evaluation community concerned with the environment‐poverty nexus should make an early effort to frame the questions that need to be answered in order for the goals to materialize, and to identify feasible approaches and methods to evaluate them.